Frequency of Abnormal Placentation in Patients with Previous Caesarean Section - Tehreem Yazdani, Tehreem Yazdani; Aliya Islam, Aliya Islam; Ghazala Nadeem, Ghazala Nadeem; Talat Hayat, Talat Hayat; Maimoona Mushtaq, Maimoona Mushtaq (Journal of Rawalpindi Medical College, 2007)
Background: To assess relationship between previous caesarean scar and subsequent development of placenta praevia and its morbid adherence. Methods: This analytical study was conducted in the Department of Gynaecology and Obstetrics, Military Hospital, Rawalpindi from 1st July to 31st December 2006. 122 pregnant women with history of previous caesarean sections beyond 32 weeks of gestation whether booked or unbooked, irrespective to number of caesarean scars with or without bleeding per vagina were included in this study. Cases with previous myomectomy, uterine repair, placental abruption, bleeding per vagina due to local causes were excluded. Patients were divided into four groups. Group A with previous one caesarean section, group B with previous, two caesarean sections, Group C previous three caesarean sections and, Group D with previous four caesarean sections. Results: Group A included 69 patients and 07 (10%) were found to have placenta praevia. In Group B 32 patients were studied and placenta praevia was diagnosed in 5 (15.6%) of them. Similarly in Group C 12 patients were studied and 4 (33.3%) had placenta praevia. The study of Group D showed placenta praevia in 3 out of 9 (33.3%) patients. There was 2 case of placenta accreta in group A, C and D and one in group B. Conclusion: The percentage of placenta praevia and morbidly adherent placenta rises with increasing number of caesarean sections.